2008
DOI: 10.1177/0961203308093071
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar ataxia in systemic lupus erythematosus

Abstract: Neuropsychiatric manifestations are commonly observed in systemic lupus erythematosus (SLE) patients; however, cerebellar involvement has rarely been reported. In the presence of acute cerebellar ataxia, etiologies related (focal edema and ischemia) and not related (infections, malignancy and paraneoplastic syndromes) to lupus have to be considered and they imply different treatment strategies. We report the clinical and radiological features of 3 SLE patients who presented with acute cerebellar ataxia. A revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 18 publications
0
31
0
2
Order By: Relevance
“…She had serological markers of highly active SLE, high titers of anti-dsDNA and low complement level. [8] Our patient had restriction on DWI and pathological evidence of infarction and vasculitis suggesting the possibility of vasculitis of the posterior inferior cerebellar artery and occlusion resulting in massive cerebellar infarction. In view of these findings, we suspected that the cerebellar infarction was due to vasculitis caused by highly active SLE.…”
Section: Massive Vasculitic Cerebellar Infarction In Patient With Sysmentioning
confidence: 57%
“…She had serological markers of highly active SLE, high titers of anti-dsDNA and low complement level. [8] Our patient had restriction on DWI and pathological evidence of infarction and vasculitis suggesting the possibility of vasculitis of the posterior inferior cerebellar artery and occlusion resulting in massive cerebellar infarction. In view of these findings, we suspected that the cerebellar infarction was due to vasculitis caused by highly active SLE.…”
Section: Massive Vasculitic Cerebellar Infarction In Patient With Sysmentioning
confidence: 57%
“…In a recent study of adult patients with newly diagnosed SLE, cerebral atrophy was found in 18% of patients and was unrelated to higher corticosteroid dosing 10 . Although cerebellar changes are associated with neurocognitive deficits in other inflammatory and ischemic disorders, there are minimal data on cerebellar involvement in patients with SLE 11,12 . Although cerebellar changes are associated with neurocognitive deficits in other inflammatory and ischemic disorders, there are minimal data on cerebellar involvement in patients with SLE 11,12 .…”
Section: Rheumatologymentioning
confidence: 99%
“…This lesion disappeared within 9 days of corticosteroid treatment. In 2008, Appenzeller et al [9] reported 3 women with SLE and acute cerebellar ataxia, who were successfully treated with intravenous corticosteroids and an immunosuppressant. Most recently, in 2014, Ghosh et al [10] described a 22-year-old girl with active SLE, who presented with lupus nephropathy and subacute pancerebellar syndrome.…”
Section: Discussionmentioning
confidence: 99%